(untitled) (Studia Prawnicze / The Legal Studies, 1983)
In socialist states there are three ways of controlling the accordance of law with the constitution: 1) vesting the parliament with its execution, 2) vesting a special presidium board (type of e.g. Council of State) with its performance, 3) setting up a special judicial authority for that purpose (constitutional tribunal). In People’s Poland up to 1976 the first of the above mentioned ways of executing control of constitutionality of law (parliamentary control) was carried out, in the years 1976-1982 - the second way (control by the Council of State), and in 1982 the third method was proclaimed, by special judicial organ. On March 26, 1982 the Diet adopted a resolution on certain changes in the Constitution consisting, i.a., in introducing a new article (33a) providing for setting up the Constitutional Tribunal. The Tribunal is to state opinions on the accordance with the Constitution of norm-setting acts of supreme state authorities and On the accordance to the laws of norm-setting acts of smaller than laws legal validity. The Tribunal is subordinate to the Diet in this respect that the Diet passes a final decision on accepting the Tribunal’s opinion on the inconformity of the law to the Constitution and - what is of a paramount importance - appoints members of the Tribunal. But after they have been appointed, they are independent and subject only to the Constitution in performing their functions. Such a position of the Tribunal does not impair the superior position of the Diet in the system of state authorities on one hand, and - on the other hand - it guarantees passing impartial decisions by the Tribunal within its competence. The structure of the Constitutional Tribunal and the system of work shall be defined in detail by the law. Thus the article deals only with the regulations by the Constitution and the authors try to explain throughout their motifs and content. Legal and constitutional solutions in Poland concerning the control of constitutionality of law have been presented against analogous solutions used in other socialist states and in relation to other mechanisms of control of legality in forming law. The authors conclude that in the so far binding state of law the Constitutional Tribunal in neither a judicial organ in the strict meaning (common or special court) nor an authority of state control (such as the Supreme Chamber of Control) but a special kind of state authority fulfilling its own functions.